2021
DOI: 10.1007/s12033-021-00348-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-29a Inhibits Colon Cancer Progression by Downregulating B7-H3 Expression: Potential Molecular Targets for Colon Cancer Therapy

Abstract: BackgroudMiR-29a belongs to one of the subtypes of miRNAs known as non-coding single-stranded RNAs, and is preferentially expressed in normal tissues. B7-H3, a member of the B7/CD28 immunoglobulin superfamily, was shown to be overexpressed in several solid malignant tumors, including colon cancer. In

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…For instance, Yan et al demonstrated that hsa-miR-125a was upregulated in human colon cancer cells (SW480) [ 57 ]. Wang et al [ 58 ] discovered that miR-29a inhibited the evolution of colon cancer by down-regulating the B7-H3 expression.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Yan et al demonstrated that hsa-miR-125a was upregulated in human colon cancer cells (SW480) [ 57 ]. Wang et al [ 58 ] discovered that miR-29a inhibited the evolution of colon cancer by down-regulating the B7-H3 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, B7-H3 protein expression correlated contrariwise with miR-29 levels in these tumors [22]. Results of different studies confirmed that miR-29 miRNAs downregulate B7-H3 expression by targeting B7-H3 3 UTR, which contains a miR-29 binding site [22,59,60]. Finally, Cheung et al demonstrated the miR-29 downregulation in NB metastatic to the CNS compared with primary tumors.…”
Section: Regulation Of B7-h3 Expression In Extracranial Pstsmentioning
confidence: 87%
“…Abnormal miRNA expression in cancer may be either detected as downor upregulation, meaning various families of these molecules could act either as oncogenes or as tumor suppressors [53]. Forasmuch as the abovementioned roles of miRNAs as regulators of cancer formation and metastasis, different studies have investigated the relationship between miRNA and B7-H3, as a carcinogenesis-associated protein, primarily expressed only in tumor tissues [22,23,59,60]. It has been noticed that a specific member of the miRNA family, miR-29a, was vastly expressed in normal tissues, but downregulated in different solid tumors, including sarcomas, NB, and brain tumors.…”
Section: Regulation Of B7-h3 Expression In Extracranial Pstsmentioning
confidence: 99%
“…Based on the above, the substance in exosomes such as miR-29a-3p may have different significance and effects. Reports have shown that the detection of miR-29a-3p in glioma can be used as a malignant marker after making a definite diagnosis (23)(24)(25), then, if possible, the glioma can be staged according to the expression of miR-29a-3p and clinical data. As miR-29a-3p expressed in peripheral blood can be used as a biomarker for the preliminary diagnosis of disease, and may be used as an early marker for disease screening, this highlights the significance of detecting it in peripheral blood (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%